Peningkatan Hasil Belajar IPS Dengan Penerapan Model Student Facilitator And Explaining Pada Kelas IV SDN 004 Bangkinang - Nasriady Hamid; Musnar Indra (Jurnal Pendidikan Tuntas, 2023)
This research was based on the low social studies learning outcomes of class IV SDN 004 Bangkinang, therefore the researchers provided a solution in the form of applying the Student Facilitator and Explaining learning model to improve student learning outcomes Recognizing the Development of Production, Communication and Transportation Technologies. The formulation of the problem in this research is how to apply the Student Facilitator and Explaining model to improve social studies learning outcomes in the material Understanding the Development of Production, Communication and Transportation Technology in class IV students at SDN 004 Bangkinang. This research was conducted in class IV SDN 004 Bangkinang. This research was conducted in two cycles and each cycle held two meetings. The subjects of this study were 16 grade IV students at SDN 004 Bangkinang, with 10 male students and 6 female students. Data collection techniques used in this study are observation, documentation, and testing techniques. Based on the results of the study it can be concluded that in cycle I it was still quite sufficient with an average of 75.93, then out of 16 students only 12 students or 75% achieved completeness individually. Student learning outcomes in cycle II were relatively good with an average of 86.87 and 15 students completed or 93.75% who achieved completeness individually. Thus it can be concluded that by applying the Student Facilitator and Explaining learning model it can improve learning outcomes Recognizing the Development of Production, Communication and Transportation Technology in class IV students at SDN 004 Bangkinang.